Hypoxia-related Y RNA fragments as a novel potential biomarker for distinguishing metastatic oral melanoma from non-metastatic oral melanoma in dogs - MD Nazmul Hasan; MD Mahfuzur Rahman; Al Asmaul Husna; Daiki Kato; Takayuki Nakagawa; Mohammad Arif; Naoki Miura (Veterinary Quarterly, 2024)
Hypoxia may promote tumor progression, and hypoxically altered noncoding RNA (ncRNA) expression may play a role in metastasis. Canine oral melanoma (COM) frequently metastasizes, and ncRNA expression under hypoxia may be clinically significant. We aimed to elucidate ncRNA fragments whose expression is altered by hypoxia in COM-derived primary KMeC and metastatic LMeC cell lines using next-generation sequencing to validate these results in qRT-PCR, and then compare expression between metastatic and non-metastatic COM. The NGS analysis and subsequent qRT-PCR validation were performed using hypoxic and normoxic KMeC and LMeC cells, and clinical samples [tumor tissue, plasma, and plasma-derived extracellular vesicles] obtained from dogs with metastatic or non-metastatic melanoma were analyzed with qRT-PCR. Y RNA was significantly decreased in metastatic LMeC cells versus primary KMeC cells in hypoxic and normoxic conditions. The expression of Y RNA was decreased in dogs with metastatic melanoma versus those with non-metastatic melanoma for all clinical sample types, reflecting the pattern found with hypoxia. Receiver operating characteristic analysis demonstrated that Y RNA level is a promising biomarker for discriminating metastatic from non-metastatic melanoma in plasma [area under the curve (AUC) = 0.993, p < 0.0001] and plasma-derived extracellular vesicles (AUC = 0.981, p = 0.0002). Overall, Y RNA may be more resistant to hypoxic stress in the metastatic than the non-metastatic state for COM. However, further investigation is required to elucidate the biological functions of Y RNA under hypoxic conditions.